Effect of Vegetation Cover Changes on the Runoff Coefficient Characteristics in the Cisangkuy Watershed, Indonesia - Ismail, Arif; Greve, Klaus; Widiawaty, Millary Agung; Dede, Moh; Nandi, Nandi (Anuário do Instituto de Geociências, 2024)
The hydrological response of a watershed is a key aspect of watershed management. Long-term monitoring is faced with a lack of empirical data. This study implements Cook’s method to determine the run-off coefficient in the Cisangkuy watershed. This method involved watershed characteristic data such as slope, soil, stream, and vegetation greenness. Run-off related to vegetation greenness, as the component of hydrological responses, data retrieved from satellite imageries (Landsat series) over 30 years using Google Earth Engine were used for this analysis. High-density vegetation areas in the Cisangkuy watershed tended to degrade from 1990 to 2010 and then increased significantly from the last ten years until 2020. Meanwhile, there was no significant change in the run-off coefficient over the 30 years measured. Non-vegetated areas increased over low- and moderate-vegetation lands, especially after 2010. The Cisangkuy watershed has a high run-off coefficient with a larger area compared to other classes with a run-off coefficient of 60-63%. In the Cisangkuy watershed, a decrease in the area of the normal category run-off coefficient contributes to an increase in this phenomenon in the high and extreme classes. The physical characteristics of the watershed, especially in terms of the utilization of water resources and flood mitigation, were examined in this study to achieve sustainable management.